PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DAN KEMANDIRIAN TERHADAP HASIL BELAJAR KOGNITIF MATEMATIKA SISWA - Siti Masitoh; Meriyati; Agus Santoso (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2022)
Problems related to the low cognitive learning outcomes of students were also found in SD Negeri 2 Wana, Melinting District, East Lampung Regency. Based on the data obtained through pre-research observations, there are still a lot of students who have not reached the Minimum Completeness Criteria (KKM) for Mathematics subjects, namely 65. This study aims to determine the effect of Jigsaw type cooperative learning on the results of students' cognitive learning outcomes, knowing the effect of independence on students' cognitive learning outcomes and knowing the interaction of the Jigsaw type cooperative learning model and independence on students' cognitive learning outcomes. This research is a research that uses a quantitative approach, with the data collection technique that the researcher chose using purposive sampling technique and the instruments used in this study using test sheets, questionnaires and documentation. Based on the results of the study in Table 4.8 above where the learning model on learning outcomes obtained a sig value of 0.000 where this is less than 0.05 then there is an influence. The results of the ANOVA test where independence on learning outcomes got a sig value of 0.024 where this was less than 0.05 then there was an effect. The interaction of learning models and independence on learning outcomes where a sig value is less than 0.05, i.e. 0.028, means that there is a positive interaction.